Lev Mykolajovych Ankin (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2021)
January 12 marked the 85th anniversary of the outstanding personality. known to a scientist in the field of trauma and orthopedics to Lev Mykolayovych Ankin.